R and D, Innovation, and Economic Growth : An Empirical Analysis - Ulku, Hulya (Washington, D.C. : International Monetary Fund, 2004)
This paper investigates the main postulations of the R and D based growth models that innovation is created in the R and D sectors and it enables sustainable economic growth, provided that there are constant returns to innovation in terms of R and D. The analysis employs various panel data techniques and uses patent and R and D data for 20 OECD and 10 Non-OECD countries for the period 1981-97. The results suggest a positive relationship between per capita GDP and innovation in both OECD and non-OECD countries, while the effect of R and D stock on innovation is significant only in the OECD countries with large markets. Although these results provide support for endogenous growth models, there is no evidence for constant returns to innovation in terms of R and D, implying that innovation does not lead to permanent increases in economic growth. However, these results do not necessarily suggest a rejection of R and D based growth models, given that neither patent nor R and D data capture the full range of innovation and R and D activities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet